The Effect of Inhaled Iloprost in Secondary Pulmonary Hypertension Due to Congenital Heart Disease (Preliminary Report) - Baysal, K; Belet, N; Muslu, A; Tekin, D (Medimond Publishing Co, 2001)
…
2nd International Congress on Heart Disease - New Trends in Research, Diagnosis and Treatment -- JUL 21-24, 2001 -- WASHINGTON, D.C.